Diagnostics is a proper field for noise control engineers - LYON, Richard H. (Archives of Acoustics, 1985)
The noise and vibration produced by machines have Tong been of concern to noise control engineers. The emphasis of such concern has been the effect of noise on people, whether hazardous or simply objectionable. The use of vibration signals to reveal operating characteristics of the machine is a new and requires a new set of measures of both the characteristics of the noise signals and the effects of the machine structure on these signals. This paper discusses the relation between noise studies and diagnostics in terms of their similarities and differences, and suggests that diagnostics is a proper field of study and work for noise control engineers.